Industrial applications of high performance computing best global practices /cedited by Anwar Osseyran, Merle Giles - Osseyran, Anwar; Giles, Merle E. (Chapman & Hall/CRC computational science series, 2015)
This book gives a comprehensive and up-to-date overview of the rapidly expanding field of the industrial use of supercomputers. It is just a pleasure reading through informative country reports and in-depth case studies contributed by leading researchers in the field.""-Jysoo Lee, Principal Researcher, Korea Institute of Science and Technology Information""From telescopes to microscopes, from vacuums to hyperbaric chambers, from sonar waves to laser beams, scientists have perpetually strived to apply technology and invention to new frontiers of scientific advancement